,.Moters" žurnalo leidimo istorijos migruojančios klaidos - Burneikienė, Genovaitė (Knygotyra, 1999)
Analyzing the history of Lithuanian periodicals presents many difficulties due to the lack of sources, archives, and memoirs concerning Lithuanian newspapers.As a result, facts without authentic verification are sometimes published, leading to errors that propagate in periodicals and scientific works.Different sources indicate various dates for the publication of the magazine Moteris. Therefore, the author has attempted to specify the accurate date of the magazine's edition in this article. The political and social reasons for the magazine’s inception were analyzed, along with the periodicals of that era and data from various sources. An analysis of the content of the first issues and a comparative review of other documents allow us to state that the first issue of the magazine Moteris was published in Vilnius in October 1920.